PEMIKIRAN PENDIDIKAN ABU A'LA AL MAUDUDI (ANALISIS KRITIS ATAS PEMBAHARUAN SISTEM PENDIDIKAN ABU A'LA AL MAUDUDI - Ma'ruf Ma'ruf (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2016)
Abul A'la al-Maududi is known as one of the leading writers of Islam in Pakistan who held the school of thought of neo-revivalist Islam, as compiled by Fazlur Rahman. Although he was known as an ulama, thinker and politician, he also contributed to the development of Islamic education. Islamic education institutions should serve as an alternative to Western modern education, in which it should not only develop science alone, but also understand the divine light through the Qur'an and Sunahtullah. This, in his words, is called the foundation of tauhid in education. He also suggested the Islamic education should be critical of modern science developed by the West. Keywords: Islamic Education, Basic of Tauhid, the Divine Light.